2015
DOI: 10.1111/nicc.12128
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards organ donor advocacy among Swedish intensive care nurses

Abstract: This study emphasizes the importance of organizing the care of PODs and their relatives in a way that promotes advocacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
2
23
1
7
Order By: Relevance
“…In fact, most consented to donate their own organs (77%), they agreed that the lack of organs is an ethical problem (88%), and they found it acceptable to propose arguments to relatives in favor of ODT (78%). These findings confirm existing research indicating that HPs working in ODT are generally highly motivated [11, 18]. …”
Section: Discussionsupporting
confidence: 90%
“…In fact, most consented to donate their own organs (77%), they agreed that the lack of organs is an ethical problem (88%), and they found it acceptable to propose arguments to relatives in favor of ODT (78%). These findings confirm existing research indicating that HPs working in ODT are generally highly motivated [11, 18]. …”
Section: Discussionsupporting
confidence: 90%
“…Nurses in the ICU may also be involved in the process of organ donation (Forsberg et al . ), increasing the number of direct and indirect activities carried out at the bedside or outside the ICU. Therefore, the interventions evaluated, as well as their weights, should be verified preliminarily according to the context and to local and national laws and regulations (Goncalves et al .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, differing cultural, social, religious, or other aspects in the specific settings of the above‐mentioned studies could also explain some of the differences found. A comparative study (Forsberg et al , ) showed that local hospitals manage to retain more experienced staff, which might explain the more positive attitudes toward donation compared to those in university hospitals, where staff turnover is higher and the number of relatively young nurses with less professional experience is greater. We believe that this effect could largely explain our results, considering the characteristics of the hospital where our survey took place.…”
Section: Discussionmentioning
confidence: 99%